(untitled) (Journal of the College of Basic Education, 2026)
The current ressarch aims to identify: 1-The level of Self Efficacy among secondary school students 2-The level of Self Efficacy among secondary school student according to gender variable (males-females) 3-The level of Self Efficacy among secondary school student according to the specialization variable (literary-scientific) The current research community consists of secondary school students the academic year2024/2023 . The research sample was (300) from high school students. In order to achieve the research objectives of the Self Efficacy, the research . And the scale became in its final form (36) paragraphs. The researcher used statistical methods (t-test for one sample, t-test for two different samples, Pearson and Wackronbach correlation coefficient). The researcher reached the following results:- 1- The secondary school students have an average level of in Self Efficacy analytics. 2ـ There are statistically diff Self Efficacy in the I, according to the change of sex, (males – females), in favor of females. 3ـ There are no Self Efficacy differences in the according to the change of specialization, (literary – scientific). In light of the results reached, the researcher formulated a number of recommendations and proposals